Oceans of energy : reservoir of power for the future - Goldin, Augusta R. (New York : Harcourt Brace Jovanovich, 1980)
Discusses the possibilities of generating electrical power from the world's oceans and of extracting natural gas from ocean kelp farms.
Includes index.
Bibliography: p. 135-139.
Booklist.
Horn Book.
School Library Journal.
7.8
Keywords: Ocean energy resources -- Juvenile literature; Ocean energy resources; Power resources; Energy resources; Marine resources